2003
DOI: 10.11598/btb.2003.0.20.178
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Activity of Enzymes Produced by Eupenicillium Javanicum and Aspergillus Niger NRRL 337 on Palm Oil Factory Wastes

Abstract: The use of palm kernel cake (PKC) and palm oil mill effluent (POME), substances from palm oil factory wastes, for monogastric is limited by their high cellulose and mannan contents. Hydrolytic enzymes have been supplemented to increase the nutrient digestibility. The maximal digestibility was obtained in the synergistic action of all enzyme components including B-D-endoglucanase (CMCase), B-D-glucosidase, B-D-mannanase, p-D-mannosidase, and oc-Dgalactosidase. Two kinds of enzymes produced by Eupenicillium java… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Biotransforming microorganisms have been shown to enhance chicken feed's chemical composition and nutritional value [79]. Purwadaria et al [80] also reported that the fermentation of agricultural byproducts improved their nutritional value. Nutrient bioavailability has been improved using solid-state fermentation (S.S.F.)…”
Section: Nutritional Composition Of Bioconverted Agricultural Byproductsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biotransforming microorganisms have been shown to enhance chicken feed's chemical composition and nutritional value [79]. Purwadaria et al [80] also reported that the fermentation of agricultural byproducts improved their nutritional value. Nutrient bioavailability has been improved using solid-state fermentation (S.S.F.)…”
Section: Nutritional Composition Of Bioconverted Agricultural Byproductsmentioning
confidence: 99%
“…Despite these challenges, using alternative feed ingredients for poultry can contribute to sustainable agricultural practices and reduce waste. The studies suggest that bioconverted residues and fermented feed can be used as broilers' feed without affecting growth performance or meat quality [80,[127][128][129].…”
Section: The Impact Of Feeding Bioconverted Byproducts On Performance...mentioning
confidence: 99%